Teaching students in clinical programs about pharmacogenomics: do they understand drug–drug interactions?. (26th July 2018) - O'Brien, Travis J; Harralson, Arthur F
Teaching the clinical implementation of pharmacogenomics to students in clinical programs first requires careful consideration of their aptitude in basic clinical pharmacologic concepts. Prior to developing training exercises on drug–gene interactions, educators must first assess student competency in identifying and managing drug–drug interactions given the similarities in identifying and managing these sources of medication error.